Forest Sector Public Expenditure Reviews : Review and Guidance Note - Fowler, Martin; Abbot, Patrick; Akroyd, Stephen; Channon, John; Dodd, Samantha (World Bank, Washington, DC, 2014)
This report and guidance note has been prepared by the program on forests (PROFOR), a multi-donor partnership housed at the World Bank, in order to build a body of knowledge and global good practice to support public expenditure reviews (PERs) in the forest sector. Understanding the processes that drive public expenditure allocations, as well assessing the efficacy of the expenditures undertaken, is crucial for ensuring that forests are properly and sustainably managed. The report reviews experience from a large number of forestry, agriculture, and related sector expenditure reviews. Based on this literature review, a set of principles and procedures have been developed to guide and support future public expenditure analyses in the forest sector. The report discusses challenges that are specific to the forest sector. Forest policy objectives tend to be a compromise between competing objectives, ranging from timber production by the private sector to conservation interests to resources for local communities and livelihoods. Balancing these competing objectives is a complex issue. In addition, where corruption and political interference are endemic, there are often significant gaps between policy plans and what is actually implemented.